Redesign of Product Packaging with Kansei Engineering: Empirical Study on Small-medium Enterprises in Indonesia - Suzianti, Amalia; Aldianto, A. (Makara Journal of Technology, 2020)
Small-medium enterprises (SMEs) in Indonesia have been proven to be one of the important pillars of the national economy. Unfortunately, some problems hinder their development, and one of the critical problems is the quality of product packaging. The packages of SME products are considered poor, dirty, and unattractive. Packaging problem is one of the factors why consumers are less interested in buying and why SME products always lose in the competition with other products. This study discusses how to employ Kansei engineering to design better SME product packaging with a focus on psychological (affective) aspects. This research concludes that there are four components that represent consumers’ desires: Attractiveness, Robustness, Handy & Green, and Lightness. The final result of this research is the creation of four new designs for a product package that satisfies each of the above components.